The patron-driven library : a practical guide for managing collections and services in the digital age - Allison, Dee Ann K.; ScienceDirect eBooks (Oxford : Chandos Pub., 2013)
"A guide for librarians to develop a new relationship with technology that preserves the core mission of libraries while responding to the needs of a new generation of library clients"--Page xxii.
Part 1. Libraries and library users changing with the times -- Chapter 1. From the White House conferences and the golden age of libraries to challenges for libraries in the age of digital information -- Chapter 2. A culture of technology -- Part 2. The rise of the librarian : service over collections -- Chapter 3. A focus on readers -- Chapter 4. Information literacy and social networks -- Chapter 5. Collaborative collections -- Chapter 6. The librarian as advocate -- Chapter 7. Metrics for decisions -- Chapter 8. The extensible library -- Chapter 9. Digital collections -- Chapter 10. Data repositories, open source and the library -- Chapter 11. The new professional librarian -- Chapter 12. Whither the library? -- Conclusion.
Includes bibliographical references (pages 309-342) and index.
Print version record.
Safari Books Online
Elsevier
Keywords: Libraries -- Aims and objectives; Libraries -- Forecasting; Libraries -- Information technology; Libraries and the Internet; Librarians -- Effect of technological innovations on; Use-driven acquisitions (Libraries); LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Librarians -- Effect of technological innovations on; Libraries -- Aims and objectives; Libraries and the Internet; Libraries -- Forecasting; Libraries -- Information technology; Use-driven acquisitions (Libraries); Electronic books